2021
DOI: 10.1108/aaaj-08-2020-4789
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a humanitarian disaster on the working approach of accountants: a study of contingent effects

Abstract: PurposeThe purpose of this paper is to investigate how a humanitarian disaster as coronavirus disease 2019 (COVID-19) shapes the working approach of accountants. This research is motivated by the call for more in-depth analyses of how COVID-19 affects the work, role and human condition of accountants. The study aims to discover the contingent effects, based on the contingency theory, on accountants' work due to a disaster like COVID-19.Design/methodology/approachThis is a qualitative study with an action resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 23 publications
8
26
0
Order By: Relevance
“…Short quotations feature in papers embedding/interspersing interviewee quotations within the authors' texts (see Section 4.2.6). Carungu et al. (2021) is an outlier in terms of the shortness of its quotations, averaging 14 words (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Short quotations feature in papers embedding/interspersing interviewee quotations within the authors' texts (see Section 4.2.6). Carungu et al. (2021) is an outlier in terms of the shortness of its quotations, averaging 14 words (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the papers reveal the different roles and perceptions of accounting and calculative practices under extreme circumstances. For instance, accounting is found to be a useful tool to respond to the immediate uncertainty posed by the outbreak of the pandemic (Carungu et al, 2021;Passetti et al, 2021;Sargiacomo et al, 2021), although some accounting and accountability systems are found not to be well received within the organization (Delfino and van der Kolk, 2021). Moreover, the papers highlight differences in the perception and use of accounting as a tool for control at a distance and for coordination.…”
Section: Accounting For Exceptional Decision-making At the Organizational Levelmentioning
confidence: 99%
“…In an attempt to reveal accountants' behaviour in situations departing from normal ones, Carungu et al (2021) provide an interpretive perspective based on action research. Via semistructured interviews and active participation of an author in a professional organization, the authors demonstrate that the pandemic generates relevant changes in the accountants' experience: some are short-term effects, while others will be better appreciated from a longterm perspective.…”
Section: Accounting For Exceptional Decision-making At the Organizational Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the use of accounting and accountability practices by governments when making extraordinary decisions in response to the pandemic (Mitchell et al , 2021; Ahrens and Ferry, 2021; Ahmad et al , 2021; Ahn and Wickramasinghe, 2021). The second is the use of accounting, numbers and calculative practices by businesses, not-for-profit organisations and charities to navigate the pandemic (Carungu et al , 2021; Velayutham et al , 2021; Delfino and van der Kolk, 2021; Passetti et al , 2021; Sargiacomo et al , 2021a; Kober and Thamber, 2021; Huber et al , 2021). The third is the role of accounting in exacerbating existing inequalities during the pandemic (Andrew et al , 2021; Christ and Burritt, 2021; Nikidehaghani and Cortese, 2021).…”
Section: The Second Special Issue: Emerging Themesmentioning
confidence: 99%